Application of simulation techniques for combined risk assessment of both geological and grade model—an example - C. E. Dohm (The Southern African Institute of Mining and Metallurgy, 2003)
The paper serves to show the importance of both a geological model and geostatistical model that support one another in mineral resource evaluation. It highlights the advantage of reference models for the geometry, the geological, statistical and geostatistical models of various orebody types and introduces a method for quantifying the combined uncertainty in these models. The example presented reveals how the above levels of information can be applied to add value to a resource evaluation process. It is a generic example in that it is the technique of combining uncertainty in the geological model (boundaries) as well as the grade model to assess the overall risk in the estimation of the resource. Data from the coal industry is used to illustrate the techniques. The geological uncertainty is considered via categorical simulations and these are combined with simulations of the variables (grades, thickness,) being estimated in the resource. The simulation techniques used are based on the application of GSLIB software1and a general discussion of the two simulation processes is included. In conclusion the paper demonstrates how the results of two types of conditional sequential simulation can be combined to produce confidence limits that take both uncertainties into consideration. This technique does not replace the resource estimation; it serves as an additional tool to quantify confidence in the resource evaluation model. The topics considered in this contribution are in terms of continuous improvement of mineral resource evaluation.